2017
DOI: 10.12659/msm.899476
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and Factors Influencing Femoral Neck Shortening in Elderly Patients After Fracture Fixation with Multiple Cancellous Screws

Abstract: BackgroundTo study the incidence of and factors influencing “neck shortening” in elderly patients treated for femoral neck fractures using multiple cancellous screws.Material/MethodsOf the 197 femoral neck fracture cases treated via closed reduction and cancellous screws fixation from January 2006 to February 2010, 110 were followed up. Patient age, gender, operative time, implantation method, reduction quality, fracture type, bone mineral density, loading time, length of hospital stay, and Harris hip score 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…These complications may result from the following factors. First, poor bone quality and thin cortices of the proximal humerus limit the tactile feedback of the drill bit [ 9 ], which makes selection of proper screw length difficult [ 10 ]. Second, the sphericity of the humeral head and diverging and converging locking screw vector make the exact localization of the screw tip using intraoperative fluoroscopy difficult [ 9 , 11 ], and make it hard to determine if the screws are inserted into the glenohumeral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…These complications may result from the following factors. First, poor bone quality and thin cortices of the proximal humerus limit the tactile feedback of the drill bit [ 9 ], which makes selection of proper screw length difficult [ 10 ]. Second, the sphericity of the humeral head and diverging and converging locking screw vector make the exact localization of the screw tip using intraoperative fluoroscopy difficult [ 9 , 11 ], and make it hard to determine if the screws are inserted into the glenohumeral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, the reoperation rate of hemiarthroplasty patients in our study was 13.3%, while it was 1%-7% Joon Soon Kang et al, Philipp von Roth et al, studies [10,14] . Our mean Harris Hip Score was 74 in the fixation patients compared to 62 and 82 in Kasettiet al, Xiaobin et al, studies [15,16] . While our mean Harris Hip Score was 86.3 in hemiarthroplasty patients compared to 77 and 86.9 in Paul T.P.W.…”
Section: Discussionmentioning
confidence: 42%
“…Sliding implants, such as OCCS, can lead to FNS, which causes abductor muscle weakness as a result of a decreased abductor moment arm [ 23 ]. Chen et al [ 24 ] reported that FNS occurred in 41.8% of elderly patients after fracture fixation with multiple cancellous sites and negatively affected postoperative joint function without affecting fracture union, whereas parallel implantation exhibited an increased shortening incidence compared with strong oblique implantation. To minimize this phenomenon, Weil et al [ 23 ] introduced the use of fully threaded screws and demonstrated that these screws decreased FNS after fixation of femoral neck fractures compared with OCCS.…”
Section: Discussionmentioning
confidence: 99%